CHILDREN'S LITERATURE AS A MOTIVATIONAL LEVER IN FFL: AN INNOVATIVE SOCIO-AFFECTIVE AND COGNITIVE APPROACH - Samir BENABDELKOUI (Analele Universităţii din Craiova. Psihologie, Pedagogie)
This study explores the impact of children's literature on FLE learning among Algerian students aged 12-13 through a pedagogical sequence based on the album "The Little Blue Camel". Drawing on motivational (Deci & Ryan) and socioconstructivist (Vygotsky) theories, the research demonstrates that this approach significantly stimulates learner engagement, improves linguistic skills, and transforms reading perceptions. Analysis of written/oral productions and interviews reveals that children's literature, through its narrative and affective dimensions, simultaneously promotes language acquisition and intercultural competency development while creating a motivating learning environment. However, the study identifies structural obstacles (lack of resources, insufficient teacher training) that call for better-planned integration of these materials into curricula. These results suggest that when systematically implemented, children's literature can become a powerful lever to reconcile academic requirements with learning enjoyment in FLE contexts, thus opening promising perspectives for renewing teaching practices in emerging Francophone countries.